Can beliefs improve mental health? A dive into resilience during pandemic times in South America - Juan-Pablo Morales; Brenda E. Ryan; Vince Polito; Gorka Navarrete; Mayte Vergara; David Huepe (Social Sciences and Humanities Open, 2024)
The association between paranormal beliefs and mental health has been extensively investigated. Nonetheless, there has been limited opportunity to examine this association in contexts characterized by high stress and social vulnerability. This study investigates the relationship between paranormal beliefs and mental health issues, particularly anxiety, depression, and stress, amidst the backdrop of the COVID-19 pandemic. Additionally, we evaluated the impact of dealing with the pandemic on rationality and assessed the subjective perception of beliefs as coping mechanisms. One hundred sixty-three participants took part in our online self-reported study. A correlational and hierarchical regression analysis shows that paranormal beliefs positively correlate with mental illness and could be predictive of them, that does not imply a causal relation. Rather, this means that in the context of the pandemic, higher levels of paranormal beliefs were associated with higher levels of anxiety, depression, and stress symptoms. Rationality was negatively correlated with paranormal beliefs, and on the contrary, those with stronger beliefs perceived their faith as a helpful tool to cope with mental health issues. Contrary to what people consciously reported, this study showed that paranormal beliefs harmed mental health during the pandemic. We acknowledge that other variables may contribute to paranormal beliefs and mental health outcomes. Although the pandemic is now, luckily enough, something from the past, and given the transient nature of the crisis, these results could be cautiously understood under the light of other stressful scenarios such as high social challenges, like extreme poverty or severe illness.